STUDI EKSPERIMEN: PENGARUH MARKETING PR TERHADAP MINAT BELI PRODUK PERBANKAN - Pane, Ivanina Zuhdi; Ardiyanti, Handrini; Amelia, Eliza (KOMUNIKOLOGI: Jurnal Ilmiah Ilmu Komunikasi, 2024)
The goal of this research is to investigate the impact of marketing public relations on purchase interest for Bank Perkreditan Rakyat products. This research was carried out using an experimental design that consisted of a pre-test and post-test system. Pre-testing is done to increase purchase interest before marketing PR intervention, and the intervention is done by providing customers with information through marketing PR. A post-test is performed to determine whether or not the purchase interest has changed following the intervention. The results of this study, based on the t-test hypothesis, show that there is a significant relationship between product purchase and marketing PR (sig. = 0.013; t = 2,649). As a result, public relations marketing has a significant impact on purchasing behavior. This research expands our understanding of marketing public relations. Furthermore, based on the results of the marketing PR theory analysis, this study concludes that understanding and applying marketing PR theory ideas can be a valuable tool for developing more efficient and effective marketing strategies, particularly in terms of increasing customer purchase interest.Keywords: marketing PR, Experimental Study, purchase interest